Policy learning in Europe: The 'open method of coordination' and laboratory federalism - Wolfgang Kerber; Martina Eckardt (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
The Open Method of Coordination (OMC) is a new governance method applied in the European Union to policy fields where the main competences still rest with the member states. The OMC should help to foster mutual learning about successful policies and promote policy transfer by identifying best practices and recommending them. By confronting this approach with the economic concept of laboratory federalism its potential for the innovation and diffusion of policies in a multi-level governance system is analysed. Both concepts use the basic idea of decentralised experimentation and mutual learning from experiences with implemented policies. Whereas the OMC organizes this learning process to a greater extent 'top-down', laboratory federalism is much more a 'bottom-up' concept. Their advantages and shortcomings in evaluating, finding and transferring best policies are discussed and the underlying insufficiencies in setting adequate incentives for adopting better policies are analysed. It is shown that under certain conditions both concepts can supplement each other.
Keywords: D7; F02; F42; H7; 330; European Union; Federalism; Open Method of Coordination; Policy Coordination; Policy Innovation; Policy Learning